Anti-Neuroinflammatory Potential of a Nectandra angustifolia (Laurel Amarillo) Ethanolic Extract - Crescitelli, Maria Carla (2023)
Microglia, the resident macrophage-like population in the CNS, plays an important role in the pathogenesis of many neurodegenerative disorders. Nectandra genus is known to produce different metabolites with anti-inflammatory, anti-oxidant and analgesic properties. Although the species Nectandra angustifolia is popularly used for the treatment of different types of inflammatory processes, its biological effects on neuroinflammation have not yet been addressed. In this study, we have investigated the role of a Nectandra angustifolia ethanolic extract (NaE) in lipopolysaccharide (LPS)-induced neuroinflammation in vitro and in vivo. In LPS-activated BV2 microglial cells, NaE significantly reduced the induced proinflammatory mediators TNF-α, IL-1β, IL-6, COX-2 and iNOS, as well as NO accumulation, while it promoted IL-10 secretion and YM-1 expression. Likewise, reduced CD14 expression levels were detected in microglial cells in the NaE+LPS group. NaE also attenuated LPS-induced ROS and lipid peroxidation build-up in BV2 cells. Mechanistically, NaE prevented NF-κB and MAPKs phosphorylation, as well as NLRP3 upregulation when added before LPS stimulation, although it did not affect the level of some proteins related to antioxidant defense such as Keap-1 and HO-1. Additionally, we observed that NaE modulated some activated microglia functions, decreasing cell migration, without affecting their phagocytic capabilities. In LPS-injected mice, NaE pre-treatment markedly suppressed the up-regulated TNF-α, IL-6 and IL-1β mRNA expression induced by LPS in brain. Our findings indicate that NaE is beneficial in preventing the neuroinflammatory response both in vivo and in vitro. NaE may regulate microglia homeostasis, not only restraining activation of LPS towards the M1 phenotype but promoting an M2 phenotype.